Control interno en los procesos de recaudación y su afectación a los estados financieros de la Empresa Pública PRODEUTEQ-EP, año-2017 - Macías Mera, María Fernanda (2018)
The purpose of internal control is to provide reasonable assurance regarding the achievement of the organizations' objectives; therefore the present research work promotes through the proposed objectives strengthen, improve and apply more effective and efficient controls within the collection process, involving the officials of Escuteq, Cecapro, Procombise and Soluteq programs of the public company Prodeuteq-EP , so that the registration of revenue from the sales that manage the programs is carried out in a timely manner, and in this way financial information can be provided to administrators that provides reliability and accuracy, with which they can make decisions that allow them to increase profitability of the company; In addition, the need to innovate the channels for promotion and dissemination of the programs and services offered by each one was known, since through the survey applied to clients it was determined that 53% of 124 clients surveyed indicated that they did not know the other goods and / or services offered by the company and that 89% of them are willing to recommend the good and / or service received; this will allow you to increase your sales and therefore obtain more income. Regarding the review of 124 income records for the collections of the programs, it was shown that only 9% was recorded in the company's accounts in a timely manner and 91% was recorded untimely of the date established in the deposit receipt.